Building Walls, Social Groups and Empires: A Study of Political Power and Compliance in the Neo-Assyrian Period - Marta Lorenzon; Caroline Wallis (Asia Anteriore Antica)
This contribution aims to use social history and social theory to investigate political power and compliance with authority in ancient Western Asia, through the case study of Neo-Assyrian imperial building projects. Our first aim is to discuss the realities of construction work in the Neo-Assyrian Empire, focusing on the building process both through literary sources and archaeological data. Our second goal is to understand the role played by these building sites in the strengthening of local and supra-local political orders, in the consolidation of social group boundaries, and in the construction of political subjectivities of the ancient social actors involved. Our reflection sheds light on the new interpretative possibilities – and challenges – that integrating social theories, archaeological work, and language technology may create.